2023
DOI: 10.1021/acsanm.3c02014
|View full text |Cite
|
Sign up to set email alerts
|

Structured Graphene Oxide/Reduced Graphene Oxide Interfaces for Improved NO2 Sensing

Abstract: Here, we demonstrate an improvement in sensitivity toward the NO2 analyte by varying the width ratio of adjacent graphene oxide (GO) and reduced graphene oxide (rGO) layers using the GO laser reduction technique. We evaluated changes brought by laser reduction in material morphology, structure, electrical characteristics, and sensing performance depending on the GO/rGO ratio, which we supported by density functional theory calculations. Our results indicate that the reduction of GO yields the appearance of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The electronic properties calculations indicate that a well-defined pattern may appear when detecting the molecules, so the systems can be considered good pollutant molecule sensors. Reports can be found about gas sensors with an ultralow detection limit, 75 where the sensitivity and selectivity depend on the surface functionalization, such as epoxy or hydroxyl groups in graphene oxide, 76 doping, and decoration that change transport properties. show the structural and electronic properties of the graphene single-atom catalyst (GSAC) on the MoS 2 (GSAC/MoS 2 ).…”
Section: Pollutant Molecules Adsorption On G/mos 2 and G/wsmentioning
confidence: 99%
“…The electronic properties calculations indicate that a well-defined pattern may appear when detecting the molecules, so the systems can be considered good pollutant molecule sensors. Reports can be found about gas sensors with an ultralow detection limit, 75 where the sensitivity and selectivity depend on the surface functionalization, such as epoxy or hydroxyl groups in graphene oxide, 76 doping, and decoration that change transport properties. show the structural and electronic properties of the graphene single-atom catalyst (GSAC) on the MoS 2 (GSAC/MoS 2 ).…”
Section: Pollutant Molecules Adsorption On G/mos 2 and G/wsmentioning
confidence: 99%
“…Combustion of fuel produces highly corrosive and acidic NO 2 gas which directly harms the human respiratory tract and increases severe respiratory infections and asthma. It is also known that long-term exposure to high ppm of NO 2 leads to chronic lung disease. NO 2 can be detected selectively by a chemiresistive method. Various techniques have been applied to enhance the NO 2 sensing response of chemiresistive materials. , For instance, Gangareddy et al recently introduced Au nano island embedded H-glass as an effective NO 2 sensor, where the exposed surface area of Au nano islands and local field effectively improved the NO 2 response . Cha and co-workers obtained noteworthy enhancement in low ppm of NO 2 response of 2D WS 2 edge functionalized multichannel carbon nanofibers due to the synergistic effect of increased surface area and porosity .…”
Section: Introductionmentioning
confidence: 99%
“…Cha and co-workers obtained noteworthy enhancement in low ppm of NO 2 response of 2D WS 2 edge functionalized multichannel carbon nanofibers due to the synergistic effect of increased surface area and porosity . Kumar et al have shown improved NO 2 sensing by increasing NO 2 physisorption by increasing the width of the GO/rGO interface . Li et al synthesized flower-like SnSe 2 /SnO 2 and showed enhanced NO 2 sensing under UV radiation .…”
Section: Introductionmentioning
confidence: 99%